Effects of New Hampshire's innovative assessment and accountability system on student achievement outcomes after three years - Carla M. Evans (Arizona State University, 2019)
New Hampshire's Performance Assessment of Competency Education (PACE) pilot received a waiver from federal statutory requirements related to state annual achievement testing starting in the 2014-15 school year. PACE is considered an "innovative" assessment and accountability system because performance assessments are used to help determine student proficiency in most federally required grades and subjects instead of the state achievement test. One key criterion for success in the early years of the PACE innovative assessment system is "no harm" on the statewide accountability test. This descriptive study examines the effect of PACE on Grades 8 and 11 mathematics and English language arts student achievement during the first three years of implementation (2014-15, 2015-16, and 2016-17 school years) and the extent to which those effects vary for certain student subgroups using results from the state's accountability tests (Smarter Balanced and SATs). Findings suggest that students in PACE schools tend to exhibit small positive effects on the Grades 8 and 11 state achievement tests in both subjects in comparison to students attending non-PACE comparison schools. Lower achieving students tended to exhibit small positive differential effects, whereas male students tended to exhibit small negative differential effects. Implications for research, policy, and practice are discussed.